COVER AND PREFACE JURNAL KONVERSI ENERGI DAN MANUFAKTUR VOL. 9 NO. 1 (2024) - Jurnal Konversi Energi dan Manufaktur Editor's (Jurnal Konversi Energi dan Manufaktur, 2024)
SUMMARY. Rohmatin et al., in their paper, identified the movements that occur when using a portable study table and analyzed indications of user posture risks that could be experienced when utilizing a portable study table. Wahyudi and Kusuma, in their paper, analyze heat rate losses due to parameter deviations according to actual conditions and calculate cost savings and possible improvements to determine the performance of PLTU Banten 3 Lontar unit 2. Medikano et al., in their paper, innovate the wrench to simplify the machine maintenance process. Prasetyo et al., in their report, designed, developed, and tested a prototype of a grain drying machine based on hybrid PLTS technology. This research focuses on drying machine power calculations, thermal analysis, grain drying efficiency, and evaluation of PLTS systems. Sukarno et al., in their paper, developed an automatic water recirculation system to save clean water use and energy consumption in tilapia cultivation using a microcontroller based on pH and turbidity values ​​(NTU). Wijianto and Alfitrah, in their paper, simulated the fluid flow in this downdraft-type gasification installation to determine the influence of heat distribution or temperature in the gasification equipment installation and the effect of the mass flow rate of cooling water on the airflow out of the reactor. Widodo and Golwa, in their paper, carried out an analysis using finite element methods (FEM) to simulate complex physical phenomena to obtain deformation and strain values ​​for HSS chisels in the turning process with ST42 steel workpieces. Nuha and Golwa, in their paper, analyzed the wear value of carbide-type tool edges in the ST41 material turning process based on the friction force between the tool and the workpiece.